Supported titanium sulfate catalyst, preparation method thereof and application of supported titanium sulfate catalyst in methyl methacrylate synthesis reaction

By using a supported titanium sulfate catalyst, the problem of low conversion and yield in methyl methacrylate production was solved, and an efficient esterification reaction was achieved, with stable catalyst structure and mild process conditions.

CN119793493AActive Publication Date: 2025-04-11CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202311308650.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-10
Publication Date
2025-04-11
Estimated Expiration
2043-10-10

AI Technical Summary

Technical Problem

In the prior art, in the production process of methyl methacrylate, the conversion rate of methacrylate is not high, the yield of methyl methacrylate is low, and the traditional catalyst has poor heat resistance, small specific surface area and pore volume, and poor reaction activity.

Method used

A supported titanium sulfate catalyst is used, which consists of illite mesoporous composite material and titanium sulfate supported, has a stable structure, a high specific surface area and pore volume, and is used for methacrylate esterification reaction.

Benefits of technology

It improves the conversion rate of methacrylic acid and the selectivity of methyl methacrylate, has stable catalyst structure, mild process conditions, easy to control, and has good product repeatability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119793493A_ABST
    Figure CN119793493A_ABST
Patent Text Reader

Abstract

The invention relates to the field of fine chemical engineering, and discloses a supported titanium sulfate catalyst, a preparation method thereof and application of the supported titanium sulfate catalyst in methyl methacrylate synthesis reaction. The supported titanium sulfate catalyst is composed of an illite mesoporous composite material and titanium sulfate supported on the illite mesoporous composite material. The illite mesoporous composite material has a one-dimensional and two-dimensional hexagonal pore channel double-pore distribution structure, the first most probable pore diameter is 2-7nm, the second most probable pore diameter is 20-40nm, the specific surface area is 150-600m < 2 > / g, and the pore volume is 0.7-1.6 cm < 3 > / g; on the basis of the total weight of the supported titanium sulfate catalyst, the content of the illite mesoporous composite material is 60-90 wt%, and the content of titanium sulfate is 10-40 wt%. The supported titanium sulfate catalyst is used for a methacrylic acid esterification reaction, and higher methacrylic acid conversion rate and methyl methacrylate selectivity can be obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of fine chemicals, and in particular to a supported titanium sulfate catalyst, a preparation method thereof and an application of the catalyst in a methyl methacrylate synthesis reaction. Background Art

[0002] As an important type of organic chemical product and organic chemical raw material, the industrial production level and production capacity of methyl methacrylate (MMA) have an important impact on the development of my country's chemical industry. MMA is mainly used in industries such as organic glass (PMMA), coatings, textiles, adhesives, leather, papermaking, floor polishing, unsaturated resin modification, methacrylate esters, wood impregnation agents, printing and dyeing auxiliaries, and plasticizers for plastics. In recent years, the demand for MMA polymers, profiles, plates, coatings, emulsions, etc. has increased at home and abroad, and the application fields are constantly expanding, which has promoted the rapid development of the MMA industry. At present, the domestic production technology of methyl methacrylate is still in its infancy. The development of methacrylate esterification catalysts and supporting processes with independent intellectual property rights is a development demand faced by my country's MMA production industry.

[0003] Esterification catalyst is the core technology of MMA production. For the esterification reaction of methacrylic acid and methanol, the traditional production process using inorganic acids such as sulfuric acid, phosphoric acid, and boric acid as catalysts has been gradually eliminated. Organic acids such as p-toluenesulfonic acid as catalysts also have the disadvantages of serious environmental pollution, low selectivity, and difficult product separation. In comparison, esterification catalysts used for multiphase reactions are currently a relatively active research field. In the latest reports, researchers have continuously tried to use acidic resins, organic tin compounds, rare earth solid superacids, Lewis acids and other catalysts in the synthesis of carboxylic esters, and have achieved meaningful experimental results. At present, acidic cation exchange resins are widely used in industry for the production of methyl methacrylate. Cation exchange resins show advantages such as good stability, high selectivity, low cost, and easy separation in esterification reactions. However, the cation exchange resin itself has poor heat resistance (generally it will decompose at temperatures not higher than 250°C), small specific surface area and pore volume, and the cation exchange resin is easy to swell. As an esterification catalyst, the reaction activity is poor and the ester yield is low. With the increasing demand for MMA, the prospect of synthesizing methyl methacrylate using green and environmentally friendly processes is broad. At present, solid-supported esterification catalysts are receiving more and more attention in the synthesis of methyl methacrylate. For researchers, developing esterification catalysts with excellent performance, improving reaction efficiency and inhibiting the formation of by-products are important future work directions. Summary of the invention

[0004] The purpose of the present invention is to overcome the problems of low methacrylic acid conversion rate and low methyl methacrylate yield in the current methyl methacrylate production process, and provide a supported titanium sulfate catalyst and a preparation method thereof and application in methyl methacrylate synthesis reaction. The supported titanium sulfate catalyst is used in methacrylic acid esterification reaction to obtain higher methacrylic acid conversion rate and methyl methacrylate selectivity.

[0005] In order to achieve the above-mentioned object, the first aspect of the present invention provides a supported titanium sulfate catalyst, wherein the supported titanium sulfate catalyst comprises an illite mesoporous composite material and titanium sulfate supported on the illite mesoporous composite material; wherein the illite mesoporous composite material has a one-dimensional and two-dimensional hexagonal pore double pore distribution structure, a first most probable pore diameter of 2-7nm, a second most probable pore diameter of 20-40nm, and a specific surface area of ​​150-600m 2 / g, pore volume 0.7-1.6cm 3 / g; and based on the total weight of the supported titanium sulfate catalyst, the content of the illite mesoporous composite material is 60-90% by weight, and the content of the titanium sulfate is 10-40% by weight.

[0006] The second aspect of the present invention provides a method for preparing the aforementioned supported titanium sulfate catalyst, wherein the preparation method comprises:

[0007] Titanium sulfate, an alcohol aqueous solution and an illite mesoporous composite material are contacted and reacted, and then the solid product after the solvent is removed is dried to obtain a supported titanium sulfate catalyst.

[0008] The third aspect of the present invention provides an application of the above-mentioned supported titanium sulfate catalyst in the synthesis reaction of methyl methacrylate.

[0009] Through the above technical solution, the technical solution of the present invention has the following advantages:

[0010] 1. The supported titanium sulfate catalyst provided by the present invention has a stable structure and does not deform or swell during the reaction. When used for synthesizing methyl methacrylate, the methacrylic acid conversion rate is high and the methyl methacrylate selectivity is high.

[0011] 2. The raw materials of the supported titanium sulfate catalyst provided by the present invention are easily available, the preparation method is simple, the conditions are easy to control, and the product has good reproducibility.

[0012] 3. When the catalyst provided by the present invention is used to synthesize methyl methacrylate, the process conditions are mild and the requirements for the reaction device are not high.

[0013] Other features and advantages of the present invention will be described in detail in the following detailed description. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 is the XRD spectrum of the illite mesoporous composite material A prepared in Example 1;

[0015] Figure 2 is a scanning electron microscope image of the illite mesoporous composite material A prepared in Example 1;

[0016] Figure 3 is the pore size distribution curve of the illite mesoporous composite material A prepared in Example 1. DETAILED DESCRIPTION

[0017] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0018] As mentioned above, the first aspect of the present invention provides a supported titanium sulfate catalyst, wherein the supported titanium sulfate catalyst comprises an illite mesoporous composite material and titanium sulfate supported on the illite mesoporous composite material; wherein the illite mesoporous composite material has a one-dimensional and two-dimensional hexagonal pore double pore distribution structure, a first most probable pore diameter of 2-7nm, a second most probable pore diameter of 20-40nm, and a specific surface area of ​​150-600m 2 / g, pore volume 0.7-1.6cm 3 / g; and based on the total weight of the supported titanium sulfate catalyst, the content of the illite mesoporous composite material is 60-90% by weight, and the content of the titanium sulfate is 10-40% by weight.

[0019] The inventors of the present invention have found that in the prior art, the esterification catalysts used to produce methyl methacrylate are divided into two categories: homogeneous and heterogeneous. Among them, homogeneous catalysts mainly include inorganic acid solutions and organic acids, and heterogeneous catalysts mainly include solid acids and cation exchange resins. The advantages of homogeneous catalysts are low price and good catalytic activity, but they are gradually eliminated due to defects such as difficulty in separating products from catalysts, more side reactions, and easy corrosion of equipment. Although solid acid esterification catalysts solve the problems of difficult product separation and serious equipment corrosion, they are rarely used in industrial production due to disadvantages such as poor catalytic activity, high reaction temperature, and low product selectivity. Compared with the above catalysts, the production of methyl methacrylate using acidic cation exchange resins as esterification catalysts is the main process for industrial applications. Resin catalysts have the advantages of high selectivity, low cost and easy separation, but the yield of methyl methacrylate is low during the esterification reaction of methyl methacrylate, and the high temperature resistance is also poor. Resin is an organic polymer material, which is easy to swell in organic solvents, easy to deform or even decompose in high temperature environments, which is the main reason for the poor temperature resistance of resin catalysts. Developing a new solid catalyst system to make up for the performance defects of resin catalysts is a good way to solve the problem.

[0020] The present invention provides a method for producing DOP by using a composite Lewis acid catalysis method. A composite Lewis acid is selected as a catalyst. This acid is a Lewis acid catalyst in the esterification process and is valued by people because of its high activity, good selectivity and mild reaction conditions. However, ordinary Lewis acids are unstable in water and are easily deactivated by reaction with water. In addition, some Lewis acids are easily soluble in organic solvents. In the esterification reaction process, the Lewis acid catalyst dissolves in the reaction system, which makes it difficult to separate the product. Titanium sulfate is a cheap and readily available inorganic compound, which belongs to a Lewis acid salt and has excellent performance when catalyzing the esterification reaction. Since no inorganic acid is involved in the reaction process, no difficult-to-treat waste liquid is generated, and the complex process processes such as neutralization, washing, decolorization and dehydration after the reaction are eliminated, the production cycle is greatly shortened, and the comprehensive production cost is greatly reduced. In addition, titanium sulfate does not belong to hazardous chemicals and has environmental advantages. However, directly using titanium sulfate as a catalyst in the methyl methacrylate synthesis reaction may cause the product to be difficult to separate because the titanium sulfate is partially dissolved in the reaction system. If a suitable carrier can be selected to well disperse the titanium sulfate, the above problems can be solved and a more efficient esterification reaction catalyst can be obtained. If you want to obtain a supported titanium sulfate catalyst with excellent performance, you must first choose a new material with excellent structural characteristics as a catalyst carrier. Illite mesoporous composite materials have a unique one-dimensional and two-dimensional hexagonal pore double pore distribution mesoporous structure, and at the same time have the structural advantages of large pore size and large pore volume, which is conducive to the diffusion of macromolecular reaction raw materials and products in the reaction, and may become a good carrier for supported titanium sulfate catalysts.

[0021] The inventors of the present invention found in the process of developing esterification catalysts that if titanium sulfate is loaded on illite mesoporous composite materials, the loaded catalyst prepared will not dissolve, swell or deform in organic solvents. The catalyst can show good catalytic activity and methyl methacrylate selectivity when used in the esterification reaction of methacrylic acid and methanol.

[0022] According to the present invention, preferably, based on the total weight of the supported titanium sulfate catalyst, the content of the illite mesoporous composite material is 65-85% by weight, and the content of the titanium sulfate is 15-35% by weight; more preferably, based on the total weight of the supported titanium sulfate catalyst, the content of the composite carrier is 70-80% by weight, and the content of the titanium sulfate is 20-30% by weight. In the present invention, the use of the above-mentioned specific content of the illite mesoporous composite material and the content of titanium sulfate can make the prepared catalyst have better catalytic activity and ester selectivity when used in the methacrylic acid esterification reaction.

[0023] According to the present invention, preferably, the illite mesoporous composite material has a first most probable pore size of 2-5 nm, a second most probable pore size of 22-30 nm, and a specific surface area of ​​250-450 m 2 / g, pore volume is 1.1-1.6cm 3 / g; More preferably, the first most probable pore size of the illite mesoporous composite material is 3-4nm, the second most probable pore size is 24-26nm, and the specific surface area is 301-349m 2 / g, pore volume is 1.4-1.6cm 3 In the present invention, the illite mesoporous composite material having the above-mentioned specific parameters is used, so that the prepared catalyst has better catalytic activity and ester selectivity when used in methacrylic acid esterification reaction.

[0024] According to the present invention, the specific surface area of ​​the supported titanium sulfate catalyst is 100-500m 2 / g, pore volume 0.5-1.5cm 3 / g; preferably, the specific surface area of ​​the supported titanium sulfate catalyst is 150-350m 2 / g, pore volume 0.7-1.4cm 3 / g; More preferably, more preferably, the specific surface area of ​​the supported titanium sulfate catalyst is 207-285m 2 / g, pore volume is 0.9-1.3cm 3 In the present invention, the supported titanium sulfate catalyst having the above-mentioned specific parameters is used, so that the catalyst has better catalytic activity and ester selectivity when used in the methacrylic acid esterification reaction.

[0025] According to the present invention, the illite mesoporous composite material can be synthesized according to the following method:

[0026] In the first step, tetramethoxysilane is contacted with an acid agent in the presence of a template agent, trimethylpentane and ethanol, and the resulting mixture is crystallized and filtered to obtain a mesoporous molecular sieve material filter cake 1;

[0027] The second step is to contact tetraethyl orthosilicate (TEOS) with hydrochloric acid in the presence of a template agent, hexadecyltrimethylammonium bromide (CTAB), and to crystallize and filter the resulting mixture to obtain a mesoporous molecular sieve material filter cake 2;

[0028] The third step is to contact the water glass with the inorganic acid, and wash and filter the resulting mixture to obtain a silica gel filter cake;

[0029] The fourth step is to ball-mill the mesoporous molecular sieve material filter cake 1, the mesoporous molecular sieve material filter cake 2, the silica gel filter cake and the illite powder together to obtain a solid powder;

[0030] Step 5, the solid powder obtained in step 4 is prepared into a slurry in the presence of deionized water and then spray-dried;

[0031] The sixth step is to heat the product obtained in the fifth step, remove the template, and obtain an illite mesoporous composite material having a dual pore distribution structure of one-dimensional and two-dimensional pores.

[0032] According to the present invention, in the preparation method of illite mesoporous composite material, the template agent in the first step can be various triblock copolymers of polyoxyethylene-polyoxypropylene-polyoxyethylene template agents conventionally used in the art, for example, the template agent can be a product of Aldrich Company named P123 with a molecular formula of EO 20 PO 70 EO 20 Template agent;

[0033] According to the present invention, in the method for preparing illite mesoporous composite material, the molar ratio of the template, ethanol, trimethylpentane and tetramethoxysilane in the first step is 1:100-500:200-500:50-200, preferably 1:200-400:250-400:70-150;

[0034] According to the present invention, in the method for preparing the illite mesoporous composite material, the acid agent in the first step is one or more of an acetic acid / sodium acetate buffer solution or a hydrochloric acid solution with a pH value of 1-6;

[0035] According to the present invention, in the method for preparing illite mesoporous composite material, preferably, the conditions for contacting tetramethoxysilane with the acid agent in the first step include: temperature of 10-60° C., time of 10-72 hours, pH value of 1-7;

[0036] According to the present invention, in the method for preparing the illite mesoporous composite material, preferably, the crystallization conditions in the first step include: a temperature of 30-150° C. and a time of 10-72 hours;

[0037] According to the present invention, in the method for preparing illite mesoporous composite materials, the molar ratio of the template, tetraethyl orthosilicate, hydrochloric acid and water in the second step is 1: (0.1-2): (2-20): (50-200), preferably 1: (0.5-1.5): (5-10): (70-150);

[0038] According to the present invention, in the method for preparing illite mesoporous composite material, preferably, the conditions for contacting the tetraethyl orthosilicate with hydrochloric acid in the second step include: temperature of 10-60° C., time of 10-72 hours, pH value of 0-1;

[0039] According to the present invention, in the method for preparing the illite mesoporous composite material, preferably, the crystallization conditions in the second step include: a temperature of 30-150° C. and a time of 10-72 hours;

[0040] According to the present invention, in the method for preparing illite mesoporous composite materials, preferably, the contact temperature in the third step is 10-60°C, and the contact time is 1-5 hours; the water glass and the inorganic acid are not specifically limited, the water glass is a solution of sodium silicate, the inorganic acid is one or more of sulfuric acid, nitric acid, and hydrochloric acid, and the pH value of the mixed solution of the water glass and the inorganic acid is 2-4; the weight ratio of the water glass: inorganic acid is 3-6:1.

[0041] According to the present invention, in the method for preparing illite mesoporous composite materials, the suction filtration separation in the third step is a method of separating liquid and solid particles well known to those skilled in the art, which utilizes air pressure to separate liquid and solid particles or a mixture of liquid and liquid.

[0042] According to one embodiment of the present invention, in the preparation method of illite mesoporous composite material, the ball milling method described in the fourth step includes: adding mesoporous molecular sieve material filter cake 1, mesoporous molecular sieve material filter cake 2, silica gel filter cake and illite powder into the ball mill of the ball mill, the inner wall of the ball mill is lined with polytetrafluoroethylene, the diameter of the grinding ball is 2-3mm, and the rotation speed is 300-500r / min. Continuously grind for 0.1-100 hours at a temperature of 15-100°C in the ball mill, and then take out the solid powder. The number of grinding balls depends on the size of the ball mill. For a ball mill of 50-150ml in size, one grinding ball can be used. The material of the grinding ball can be agate or polytetrafluoroethylene, preferably agate.

[0043] According to the present invention, in the method for preparing the illite mesoporous composite material, the spray drying method in the fifth step comprises: mixing the ball-milled solid powder with deionized water to prepare a slurry at a temperature of 25-60° C., adding the slurry into an atomizer and rotating it at a high speed of 10000-15000 r / min, preferably 12000 r / min;

[0044] According to the present invention, in the method for preparing illite mesoporous composite materials, the conditions for removing the template in the sixth step are not particularly limited. For example, the temperature may be 400-600° C. and the time may be 10-80 hours.

[0045] The second aspect of the present invention provides a method for preparing the aforementioned supported titanium sulfate catalyst, characterized in that the preparation method comprises:

[0046] Titanium sulfate, an alcohol aqueous solution and an illite mesoporous composite material are contacted and reacted, and then the solid product after the solvent is removed is dried to obtain a supported titanium sulfate catalyst.

[0047] According to the present invention, the alcohol aqueous solution is a methanol-water mixed solution, an ethanol-water mixed solution or an isobutanol-water mixed solution.

[0048] According to the present invention, the weight ratio of alcohol to water in the alcohol aqueous solution is 1:(0.1-10), preferably 1:(0.2-5).

[0049] According to the present invention, the weight ratio of the titanium sulfate, the alcohol aqueous solution and the illite mesoporous composite material is 1:(3-100):(1.5-9), preferably 1:(5-20):(1.8-6).

[0050] According to the present invention, the contact reaction conditions include: a temperature of 50-90° C., preferably 60-80° C.; a time of 0.5-12 h, preferably 1-8 h. Preferably, in order to achieve a better mixing effect, rapid stirring or ultrasonic means can be used to improve the mixing efficiency during the contact reaction.

[0051] According to the present invention, the method for removing the solvent has no special requirements and can be a method known in the art, for example, vacuum drying, heating and evaporation during stirring to remove the solvent, or using a rotary evaporator to evaporate the solvent.

[0052] According to the present invention, the drying conditions include: temperature of 60-120° C., preferably 80-110° C.; time of 1-30 h, preferably 2-16 h.

[0053] The third aspect of the present invention provides an application of the above-mentioned supported titanium sulfate catalyst in the synthesis reaction of methyl methacrylate.

[0054] According to the present invention, the use comprises: contacting methacrylic acid and methanol with a supported titanium sulfate catalyst simultaneously.

[0055] In the present invention, the contact conditions of methacrylic acid and methanol with the catalyst include: the contact temperature is 40-150°C, preferably 60-120°C; the contact pressure is 0.01-5MPa, preferably 0.1-3Mpa; the mass space velocity of methacrylic acid is 0.01-30h -1 , preferably 0.1-10h -1 ; The mass space velocity of methanol is 0.01-50h -1 , preferably 0.1-30h -1 .

[0056] The present invention will be described in detail below through examples.

[0057] In the following examples and comparative examples:

[0058] The small-angle XRD test of the sample was carried out on a D8 ADVANCE high-power rotating target X-ray diffractometer produced by BRUKER AXS of Germany, with a scanning range of 0.5-10°.

[0059] The pore structure parameter analysis of the samples was carried out on an ASAP2020-M+C adsorption instrument purchased from Micromeritics, Inc., USA. The samples were vacuum degassed at 40°C for 4 hours before measurement, and the specific surface area of ​​the samples was calculated using the BET method, and the pore volume was calculated using the BJH model.

[0060] The scanning electron microscope images of the samples were obtained using an XL-30 field emission environmental scanning electron microscope produced by FEI Company in the United States.

[0061] The elemental analysis experiment of the samples was carried out on an EagleⅢ energy dispersive X-ray fluorescence spectrometer produced by EDAX, USA.

[0062] The rotary evaporator was produced by IKA of Germany, model RV10 digital.

[0063] The drying oven was produced by Shanghai Yiheng Scientific Instrument Co., Ltd., model DHG-9030A.

[0064] The muffle furnace is produced by CARBOLITE, model CWF1100.

[0065] The polyoxyethylene-polyoxypropylene-polyoxyethylene triblock copolymer (P123) used in the examples and comparative examples was purchased from Sigma-Aldrich Chemistry; the other reagents used in the examples and comparative examples were purchased from Sinopharm Chemical Reagent Co., Ltd., and the reagent purity was analytical grade.

[0066] Example 1

[0067] (1) Preparation of illite mesoporous composite materials

[0068] 11.6 g (0.002 mol) of triblock copolymer surfactant P123 and 27.6 g (0.6 mol) of ethanol were added to 300 ml of acetic acid and sodium acetate buffer with a pH value of 4, and stirred at 30°C until P123 was completely dissolved. Then, 60 g (0.52 mol) of trimethylpentane was added to the obtained solution, and stirred at 30°C for 8 h. Then, 30.4 g (0.2 mol) of tetramethoxysilane was added thereto, and stirred at 30°C and a pH value of 4.5 for 20 h. Then, the obtained solution was transferred to a polytetrafluoroethylene-lined reactor, crystallized at 60°C for 24 h, and then filtered and washed with deionized water for 4 times, and then filtered to obtain a mesoporous molecular sieve material filter cake 1 having a one-dimensional hexagonal pore single pore distribution structure;

[0069] 36.4 g (0.1 mol) of hexadecyltrimethylammonium bromide (CTAB) was added to 180 g of double distilled water, and stirred at 30°C for 2 h to obtain a homogeneous solution. The pH value of the solution was adjusted to between 0 and 1 with hydrochloric acid, and 20.8 g (0.1 mol) of tetraethyl orthosilicate (TEOS) was slowly added dropwise. After stirring for 36 hours, the mixture was transferred to a polytetrafluoroethylene-lined kettle and crystallized at 80°C for 40 h. Finally, the product was filtered and washed, and the mesoporous molecular sieve material filter cake 2 with a two-dimensional hexagonal pore single pore distribution structure was obtained by suction filtration.

[0070] A 15 wt % water glass solution and a 12 wt % sulfuric acid solution were mixed in a weight ratio of 4:1 and contact-reacted at 30° C. for 2 hours, and then the pH value was adjusted to 3 with 98 wt % concentrated sulfuric acid. The obtained reaction mass was then filtered and washed with distilled water until the sodium ion content was less than 0.02 wt %, to obtain a silica gel filter cake.

[0071] Put the prepared 5g mesoporous molecular sieve material cake 1, 5g mesoporous molecular sieve material cake 2, 10g silica gel filter cake and 10g illite into a 100ml ball mill, wherein the ball mill is made of polytetrafluoroethylene, the grinding ball is made of agate, the diameter of the grinding ball is 3mm, the number is 1, and the rotation speed is 400r / min. Close the ball mill, and mill for 1 hour at a temperature of 60°C in the ball mill to obtain a solid powder. Mix the above solid powder with 30 grams of deionized water, spray dry at 200°C, and the atomizer rotation speed is 12000r / min. The product obtained after spray drying is calcined at 500°C in a muffle furnace for 30 hours to remove the template to obtain illite mesoporous composite material A.

[0072] The specific surface area of ​​illite mesoporous composite material A is 316 m 2 / g, and the pore volume is 1.5ml / g.

[0073] Figure 1 This is the XRD spectrum of the illite mesoporous composite material A prepared in Example 1. From the small-angle peaks appearing in the XRD spectrum, it can be seen that the illite mesoporous composite material A has a one-dimensional and two-dimensional hexagonal pore double pore distribution structure that is unique to mesoporous materials.

[0074] Figure 2 This is a SEM scanning electron microscope image of the microscopic morphology of the illite mesoporous composite material A prepared in Example 1. As can be seen from the figure, the microscopic morphology of the illite mesoporous composite material A is spherical, and the particle diameter is between 30-60 μm.

[0075] Figure 3 : is the pore size distribution curve of the illite mesoporous composite material A prepared in Example 1. It can be seen that the illite mesoporous composite material A has an obvious dual pore distribution structure, the first most probable pore size is 3.5 nm, and the second most probable pore size is 25 nm.

[0076] (2) Preparation of supported titanium sulfate catalyst

[0077] In a round-bottom flask, 2.6 g of titanium sulfate, 15 g of ethanol and 15 g of water were mixed, heated to 60 ° C in a water bath and stirred for 10 hours to obtain a transparent aqueous solution. 7.4 g of illite mesoporous composite material A was added to the above transparent aqueous solution, heated to 70 ° C, and refluxed and stirred for 3 hours. After the reaction, the solvent was removed by a rotary evaporator, and the solid product was dried in air at 100 ° C for 8 hours to obtain a supported titanium sulfate catalyst A.

[0078] The specific surface area of ​​supported titanium sulfate catalyst A is 241m 2 / g, and the pore volume is 1.1 ml / g.

[0079] Based on the total weight of the supported titanium sulfate catalyst A, the content of the illite mesoporous composite material A was 74.6% by weight, and the content of the titanium sulfate was 25.4% by weight.

[0080] (3) Catalyst reaction performance evaluation

[0081] The esterification performance of the catalyst was evaluated in a fixed bed reactor. 5 g of supported titanium sulfate catalyst A was loaded into a stainless steel fixed bed reactor with an inner diameter of 8 mm, the reaction temperature was 90°C, the reaction pressure was 0.5 MPa, and the weight space velocity of methacrylic acid was 1 h -1 , the weight space velocity of methanol is 2.7h -1 The reaction time was 20 hours. After cooling, the product was analyzed by an Agilent 7890A gas chromatograph equipped with a FFAP capillary column and a hydrogen flame detector (FID), using programmed temperature and correction factors for quantitative analysis. The methacrylic acid conversion rate was 96.8%, and the selectivity of methyl methacrylate was 99.8%.

[0082] Example 2

[0083] (1) Preparation of illite mesoporous composite materials

[0084] 11.6 g (0.002 mol) of triblock copolymer surfactant P123 and 18.4 g (0.4 mol) of ethanol were added to 200 ml of acetic acid and sodium acetate buffer with a pH value of 4, and stirred at 10°C until P123 was completely dissolved. Then, 57.6 g (0.5 mol) of trimethylpentane was added to the obtained solution, and stirred at 10°C for 24 hours. Then, 21.3 g (0.14 mol) of tetramethoxysilane was added thereto, and stirred at 10°C and pH value of 4.3 for 48 hours. Then, the obtained solution was heated to 30°C, crystallized under stirring for 72 hours, and then filtered and washed with deionized water for 8 times, and then filtered to obtain a mesoporous molecular sieve material filter cake 1 having a one-dimensional hexagonal pore single pore distribution structure;

[0085] Add 36.4g (0.1mol) of hexadecyltrimethylammonium bromide (CTAB) to 126g of double distilled water, stir at 10°C for 3h to obtain a homogeneous solution, adjust the pH value of the solution to between 0-1 with hydrochloric acid, and slowly add 10.4g (0.05mol) of tetraethyl orthosilicate (TEOS). After continuing to stir for 66 hours, the mixture is heated to 30°C and crystallized under stirring for 72h. Finally, the product is filtered and washed, and the mesoporous molecular sieve material filter cake 2 with a two-dimensional hexagonal pore single pore distribution structure is obtained by suction filtration.

[0086] A 15 wt % water glass solution and a 12 wt % sulfuric acid solution were mixed in a weight ratio of 3:1 and contact-reacted at 10° C. for 5 hours, and then the pH value was adjusted to 2 with 98 wt % concentrated sulfuric acid. The obtained reaction mass was then filtered and washed with distilled water until the sodium ion content was less than 0.02 wt %, to obtain a silica gel filter cake.

[0087] Put the above-prepared 5g mesoporous molecular sieve material filter cake 1, 5g mesoporous molecular sieve material filter cake 2, 10g silica gel filter cake and 10g illite into a 100ml ball mill, wherein the ball mill is made of polytetrafluoroethylene, the grinding ball is made of agate, the diameter of the grinding ball is 3mm, the number is 1, and the rotation speed is 400r / min. Close the ball mill, and mill for 1 hour at a temperature of 60°C in the ball mill to obtain a solid powder. Mix the above solid powder with 30 grams of deionized water, spray dry at 200°C, and the atomizer rotation speed is 12000r / min. The product obtained after spray drying is calcined at 400°C in a muffle furnace for 80 hours to remove the template to obtain illite mesoporous composite material B.

[0088] The specific surface area of ​​illite mesoporous composite material B is 301m 2 / g, the pore volume is 1.4ml / g, the first most probable pore diameter is 3nm, and the second most probable pore diameter is 24nm.

[0089] (2) Preparation of supported titanium sulfate catalyst

[0090] In a round-bottom flask, 3g of titanium sulfate, 5g of methanol and 15g of water were mixed, heated to 60°C in a water bath and stirred for 10h to obtain a transparent aqueous solution. 7g of illite mesoporous composite material B was added to the above transparent aqueous solution, heated to 80°C, and refluxed and stirred for 1 hour. After the reaction, the solvent was removed by a rotary evaporator, and the solid product was dried in air at 110°C for 2 hours to obtain a supported titanium sulfate catalyst B.

[0091] The specific surface area of ​​supported titanium sulfate catalyst B is 207m 2 / g, and the pore volume is 0.9ml / g.

[0092] Based on the total weight of the supported titanium sulfate catalyst B, the content of the illite mesoporous composite material B was 70% by weight, and the content of the titanium sulfate was 30% by weight.

[0093] (3) Catalyst reaction performance evaluation

[0094] The esterification performance of catalyst B was tested according to the method of step (3) in Example 1. The conversion rate of methacrylic acid was 97%, and the selectivity of methyl methacrylate was 99.6%.

[0095] Example 3

[0096] (1) Preparation of illite mesoporous composite materials

[0097] 11.6 g (0.002 mol) of triblock copolymer surfactant P123 and 36.8 g (0.8 mol) of ethanol were added to 450 ml of acetic acid and sodium acetate buffer with a pH value of 4, and stirred at 60° C. until P123 was completely dissolved, and then 92.3 g (0.8 mol) of trimethylpentane was added to the obtained solution, and stirred at 60° C. for 2 h, and then 45.6 g (0.3 mol) of tetramethoxysilane was added thereto, and stirred at 60° C. and pH value of 4.8 for 8 h, and then the obtained solution was heated to 150° C., crystallized under stirring for 10 h, and then filtered and washed with deionized water for 6 times, and then filtered to obtain a mesoporous molecular sieve material filter cake 1 having a one-dimensional hexagonal pore single pore distribution structure;

[0098] Add 36.4g (0.1mol) of hexadecyltrimethylammonium bromide (CTAB) to 270g of double distilled water, stir at 60°C for 1h to obtain a homogeneous solution, adjust the pH value of the solution to between 0-1 with hydrochloric acid, and slowly add 31.2g (0.15mol) of tetraethyl orthosilicate (TEOS). After continuing to stir for 9 hours, heat the mixture to 150°C and crystallize for 10h under stirring. Finally, filter and wash the product, and obtain a mesoporous molecular sieve material filter cake 2 with a two-dimensional hexagonal pore single pore distribution structure by suction filtration.

[0099] A 15 wt % water glass solution and a 12 wt % sulfuric acid solution were mixed in a weight ratio of 6:1 and contacted and reacted at 60° C. for 1 hour, and then the pH value was adjusted to 4 with 98 wt % concentrated sulfuric acid. The obtained reaction mass was then filtered and washed with distilled water until the sodium ion content was less than 0.02 wt %, to obtain a silica gel filter cake.

[0100] Put the above-prepared 5g mesoporous molecular sieve material filter cake 1, 5g mesoporous molecular sieve material filter cake 2, 10g silica gel filter cake and 10g illite into a 100ml ball mill, wherein the ball mill is made of polytetrafluoroethylene, the grinding ball is made of agate, the diameter of the grinding ball is 3mm, the number is 1, and the rotation speed is 500r / min. Close the ball mill, and mill for 3 hours at a temperature of 40°C in the ball mill to obtain a solid powder. Mix the above solid powder with 30 grams of deionized water, spray dry at 200°C, and the atomizer rotation speed is 12000r / min. The product obtained after spray drying is calcined at 600°C in a muffle furnace for 10 hours to remove the template to obtain illite mesoporous composite material C.

[0101] The specific surface area of ​​illite mesoporous composite material C is 349 m 2 / g, the pore volume is 1.6ml / g, the first most probable pore diameter is 4nm, and the second most probable pore diameter is 26nm.

[0102] (2) Preparation of supported titanium sulfate catalyst

[0103] In a round-bottom flask, 2g of titanium sulfate, 25g of isobutanol and 5g of water were mixed, heated to 60°C in a water bath and stirred for 10 hours to obtain a transparent aqueous solution. 8g of illite mesoporous composite material C was added to the above transparent aqueous solution, the temperature was maintained at 60°C, and the reaction was refluxed and stirred for 8 hours. After the reaction, the solvent was removed by a rotary evaporator, and the solid product was dried in air at 80°C for 16 hours to obtain a supported titanium sulfate catalyst C.

[0104] The specific surface area of ​​supported titanium sulfate catalyst C is 285m 2 / g, and the pore volume is 1.3ml / g.

[0105] Based on the total weight of the supported titanium sulfate catalyst C, the content of the illite mesoporous composite material C is 80% by weight, and the content of the titanium sulfate is 20% by weight.

[0106] (3) Catalyst reaction performance evaluation

[0107] The esterification performance of catalyst C was tested according to the method of step (3) in Example 1. The methacrylic acid conversion was 96.7%, and the selectivity of methyl methacrylate was 99.7%.

[0108] Example 4

[0109] The supported titanium sulfate catalyst D was prepared in the same manner as in Example 1, except that the preparation conditions of the catalyst in step (2) of Example 1 were changed, specifically:

[0110] In a round-bottom flask, 3.5 g of titanium sulfate, 20 g of ethanol and 15 g of water were mixed, heated to 60 ° C in a water bath and stirred for 10 hours to obtain a transparent aqueous solution. 6.5 g of illite mesoporous composite material A was added to the above transparent aqueous solution, heated to 70 ° C, and refluxed and stirred for 3 hours. After the reaction, the solvent was removed by a rotary evaporator, and the solid product was dried in air at 100 ° C for 8 hours to obtain a supported titanium sulfate catalyst D.

[0111] The specific surface area of ​​supported titanium sulfate catalyst D is 153 m 2 / g, and the pore volume is 0.7ml / g.

[0112] Based on the total weight of the supported titanium sulfate catalyst D, the content of the illite mesoporous composite material A was 65% by weight, and the content of the titanium sulfate was 35% by weight.

[0113] The catalytic performance of Catalyst D was tested according to the esterification reaction performance evaluation method of step (3) in Example 1. The methacrylic acid conversion rate was 95.4%, and the selectivity of methyl methacrylate was 99.2%.

[0114] Example 5

[0115] The supported titanium sulfate catalyst E was prepared in the same manner as in Example 3, except that the preparation conditions of the catalyst in step (2) of Example 3 were changed, specifically:

[0116] In a round-bottom flask, 1.5 g of titanium sulfate, 25 g of isobutanol and 5 g of water were mixed, heated to 60 ° C in a water bath and stirred for 10 hours to obtain a transparent aqueous solution. 8.5 g of illite mesoporous composite material C was added to the above transparent aqueous solution, the temperature was maintained at 60 ° C, and refluxed and stirred for 8 hours. After the reaction, the solvent was removed by a rotary evaporator, and the solid product was dried in air at 80 ° C for 16 hours to obtain a supported titanium sulfate catalyst E.

[0117] The specific surface area of ​​supported titanium sulfate catalyst E is 316 m 2 / g, and the pore volume is 1.4ml / g.

[0118] Based on the total weight of the supported titanium sulfate catalyst E, the content of the illite mesoporous composite material C was 85% by weight, and the content of the titanium sulfate was 15% by weight.

[0119] The catalytic performance of Catalyst E was tested according to the esterification reaction performance evaluation method of step (3) in Example 1. The methacrylic acid conversion rate was 95.2%, and the selectivity of methyl methacrylate was 99%.

[0120] Example 6

[0121] The supported titanium sulfate catalyst F was prepared in the same manner as in Example 1, except that the preparation conditions of the catalyst in step (2) of Example 1 were changed, specifically:

[0122] In a round-bottom flask, 4g of titanium sulfate, 5g of ethanol and 15g of water were mixed, heated to 60°C in a water bath and stirred for 10h to obtain a transparent aqueous solution. 6g of illite mesoporous composite material A was added to the above transparent aqueous solution, heated to 70°C, and refluxed and stirred for 3 hours. After the reaction, the solvent was removed by a rotary evaporator, and the solid product was dried in air at 100°C for 8 hours to obtain a supported titanium sulfate catalyst F.

[0123] The specific surface area of ​​supported titanium sulfate catalyst F is 124 m 2 / g, and the pore volume is 0.5ml / g.

[0124] Based on the total weight of the supported titanium sulfate catalyst F, the content of the illite mesoporous composite material A was 60% by weight, and the content of the titanium sulfate was 40% by weight.

[0125] The catalytic performance of Catalyst F was tested according to the esterification reaction performance evaluation method of step (3) in Example 1. The methacrylic acid conversion rate was 94.4%, and the selectivity of methyl methacrylate was 98.3%.

[0126] Example 7

[0127] The supported titanium sulfate catalyst G was prepared in the same manner as in Example 3, except that the preparation conditions of the catalyst in step (2) of Example 3 were changed, specifically:

[0128] In a round-bottom flask, 1g of titanium sulfate, 15g of isobutanol and 5g of water were mixed, heated to 60°C in a water bath and stirred for 10 hours to obtain a transparent aqueous solution. 9g of illite mesoporous composite material C was added to the above transparent aqueous solution, the temperature was maintained at 60°C, and the reaction was refluxed and stirred for 8 hours. After the reaction, the solvent was removed by a rotary evaporator, and the solid product was dried in air at 100°C for 8 hours to obtain a supported titanium sulfate catalyst G.

[0129] The specific surface area of ​​supported titanium sulfate catalyst G is 329m 2 / g, and the pore volume is 1.5ml / g.

[0130] Based on the total weight of the supported titanium sulfate catalyst G, the content of the illite mesoporous composite material C was 90 weight %, and the content of the titanium sulfate was 10 weight %.

[0131] The catalytic performance of Catalyst G was tested according to the esterification reaction performance evaluation method of step (3) in Example 1. The methacrylic acid conversion rate was 94.2%, and the selectivity of methyl methacrylate was 98.5%.

[0132] Comparative Example 1

[0133] The supported titanium sulfate catalyst D1 was prepared in the same manner as in Example 1, except that the preparation conditions of the catalyst in step (2) of Example 1 were changed, specifically:

[0134] In a round-bottom flask, 6g of titanium sulfate, 5g of ethanol and 15g of water were mixed, heated to 60°C in a water bath and stirred for 10h to obtain a transparent aqueous solution. 4g of illite mesoporous composite material A was added to the above transparent aqueous solution, heated to 70°C, and refluxed and stirred for 3 hours. After the reaction, the solvent was removed by a rotary evaporator, and the solid product was dried in air at 100°C for 8 hours to obtain a supported titanium sulfate catalyst D1.

[0135] The specific surface area of ​​supported titanium sulfate catalyst D1 is 92 m2 / g, and the pore volume is 0.4ml / g.

[0136] Based on the total weight of the supported titanium sulfate catalyst D1, the content of the illite mesoporous composite material A was 40% by weight, and the content of the titanium sulfate was 60% by weight.

[0137] The catalytic performance of catalyst D1 was tested according to the esterification reaction performance evaluation method of step (3) in Example 1. The methacrylic acid conversion rate was 81.4%, and the selectivity of methyl methacrylate was 94.8%.

[0138] Comparative Example 2

[0139] The supported titanium sulfate catalyst D2 was prepared in the same manner as in Example 3, except that the preparation conditions of the catalyst in step (2) of Example 3 were changed, specifically:

[0140] In a round-bottom flask, 0.5 g of titanium sulfate, 15 g of isobutanol and 5 g of water were mixed, heated to 60 ° C in a water bath and stirred for 10 hours to obtain a transparent aqueous solution. 9.5 g of illite mesoporous composite material C was added to the above transparent aqueous solution, the temperature was maintained at 60 ° C, and refluxed and stirred for 8 hours. After the reaction, the solvent was removed by a rotary evaporator, and the solid product was dried in air at 100 ° C for 8 hours to obtain a supported titanium sulfate catalyst D2.

[0141] Based on the total weight of the supported titanium sulfate catalyst D2, the content of the illite mesoporous composite material C was 95% by weight, and the content of titanium sulfate was 5% by weight.

[0142] The catalytic performance of catalyst D2 was tested according to the esterification reaction performance evaluation method of step (3) in Example 1. The methacrylic acid conversion rate was 72.8%, and the selectivity of methyl methacrylate was 95.4%.

[0143] Comparative Example 3

[0144] Step (1) in Example 1 was cancelled, and the illite mesoporous composite material A in step (2) in Example 1 was replaced with commercially available silica (purchased from Qingdao Hailang Silica Gel Desiccant Factory, with a specific surface area of ​​329 m 2 / g, pore volume 0.6cm 3 / g) to obtain catalyst D3.

[0145] Based on the total weight of the catalyst D3, the content of commercially available silicon dioxide was 75% by weight and the content of titanium sulfate was 25% by weight.

[0146] The catalytic performance of catalyst D3 was tested according to the esterification reaction performance evaluation method of step (3) in Example 1. The methacrylic acid conversion rate was 89.4%, and the selectivity of methyl methacrylate was 95.2%.

[0147] Comparative Example 4

[0148] Step (1) and step (2) in Example 1 were eliminated, and the catalytic performance of the resin catalyst was tested according to the methacrylic acid esterification reaction performance evaluation method in step (3) in Example 1. The resin catalyst was purchased from Kairui Environmental Protection Technology Co., Ltd., model D009.

[0149] The methacrylic acid conversion was 87.6%, and the selectivity of methyl methacrylate was 97.2%.

[0150] Comparative Example 5

[0151] Catalyst D5 was prepared in the same manner as in Example 1, except that in step (2), sodium sulfate was loaded instead of titanium sulfate. Based on the total weight of catalyst D5, the content of illite mesoporous composite material A was 75% by weight, and the content of sodium sulfate was 25% by weight.

[0152] The catalytic performance of catalyst D5 was tested according to the esterification reaction performance evaluation method of step (3) in Example 1. The methacrylic acid conversion rate was 60.7%, and the selectivity of methyl methacrylate was 81.5%.

[0153] Comparative Example 6

[0154] Catalyst D6 was prepared in the same manner as in Example 1, except that the preparation of the illite mesoporous composite material in step (1) was omitted, and in step (2), "7.4 g of the illite mesoporous composite material A" was replaced by "7.4 g of all-silicon silicalite-1 zeolite molecular sieve, and the specific surface area of ​​the replaced carrier all-silicon silicalite-1 zeolite molecular sieve was 384 m 2 / g, pore volume is 0.29ml / g, and the most probable pore diameter is 0.55nm".

[0155] The catalytic performance of catalyst D6 was tested according to the esterification reaction performance evaluation method of step (3) in Example 1. The methacrylic acid conversion rate was 80.6%, and the selectivity of methyl methacrylate was 94.3%.

[0156] It can be seen from the above results that the supported titanium sulfate catalyst provided by the present invention can directly convert methacrylic acid and methanol into methyl methacrylate, thereby obtaining a higher methacrylic acid conversion rate and methyl methacrylate selectivity.

[0157] In Comparative Example 1, the content of illite mesoporous composite material in the supported titanium sulfate catalyst is too low and the content of titanium sulfate is too high. Since the active component titanium sulfate on the catalyst is unevenly dispersed on the carrier and the utilization efficiency of active sites is low during the reaction, the conversion rate of methacrylic acid is low and the selectivity of methyl methacrylate is low.

[0158] In Comparative Example 2, the content of illite mesoporous composite material in the supported titanium sulfate catalyst is too high. Due to the low content of titanium sulfate, the active component on the catalyst, there are insufficient active sites during the reaction, resulting in low methacrylic acid conversion and low selectivity for methyl methacrylate.

[0159] In Comparative Example 3, the illite mesoporous composite material specifically defined in the present invention was not used, but commercially available silica was used. Due to the irregular pore structure of the commercially available silica and the uneven dispersion of the active components on the carrier surface, the methacrylic acid conversion rate was low and the selectivity of methyl methacrylate was low.

[0160] In Comparative Example 4, the supported titanium sulfate catalyst provided by the present invention was not used, but a commercially available resin material was used to carry out the synthesis reaction of methyl methacrylate. The methacrylic acid conversion rate and methyl methacrylate selectivity of the resin catalyst were lower than those of the supported titanium sulfate catalyst provided by the present invention.

[0161] In Comparative Example 5, the active component of the supported esterification catalyst is not titanium sulfate but sodium sulfate. Due to the poor esterification catalytic performance of sodium sulfate, the conversion rate of methacrylic acid is low and the selectivity of methyl methacrylate is low.

[0162] In Comparative Example 6, in the supported esterification catalyst, since the carrier is an all-silicon silicalite-1 zeolite molecular sieve carrier, the carrier is a microporous material with a maximum pore size of only 0.55 nm, which is not conducive to the loading and dispersion of the active component; resulting in low methacrylic acid conversion and low selectivity for methyl methacrylate.

[0163] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A supported titanium sulfate catalyst, characterized in that The supported titanium sulfate catalyst comprises an illite mesoporous composite material and titanium sulfate supported on the illite mesoporous composite material; wherein the illite mesoporous composite material has a one-dimensional and two-dimensional hexagonal pore double pore distribution structure, a first most probable pore diameter of 2-7 nm, a second most probable pore diameter of 20-40 nm, and a specific surface area of ​​150-600 m 2 / g, pore volume 0.7-1.6cm 3 / g; and based on the total weight of the supported titanium sulfate catalyst, the content of the illite mesoporous composite material is 60-90% by weight, and the content of the titanium sulfate is 10-40% by weight.

2. The supported titanium sulfate catalyst according to claim 1, wherein Based on the total weight of the supported titanium sulfate catalyst, the content of the illite mesoporous composite material is 65-85% by weight, and the content of the titanium sulfate is 15-35% by weight; Preferably, based on the total weight of the supported titanium sulfate catalyst, the content of the composite carrier is 70-80% by weight, and the content of the titanium sulfate is 20-30% by weight.

3. The supported titanium sulfate catalyst according to claim 1 or 2, wherein The illite mesoporous composite material has a first most probable pore size of 2-5 nm, a second most probable pore size of 22-30 nm, and a specific surface area of ​​250-450 m 2 / g, pore volume is 1.1-1.6cm 3 / g; More preferably, the illite mesoporous composite material has a first most probable pore size of 3-4 nm, a second most probable pore size of 24-26 nm, and a specific surface area of ​​301-349 m 2 / g, pore volume is 1.4-1.6cm 3 / g.

4. The supported titanium sulfate catalyst according to any one of claims 1 to 3, wherein The specific surface area of ​​the supported titanium sulfate catalyst is 100-500m 2 / g, pore volume 0.5-1.5cm 3 / g; Preferably, the specific surface area of ​​the supported titanium sulfate catalyst is 150-350m 2 / g, pore volume 0.7-1.4cm 3 / g; More preferably, the specific surface area of ​​the supported titanium sulfate catalyst is 207-285m 2 / g, pore volume is 0.9-1.3cm 3 / g.

5. A method for preparing a supported titanium sulfate catalyst according to any one of claims 1 to 4, characterized in that: The preparation method comprises: Titanium sulfate, an alcohol aqueous solution and an illite mesoporous composite material are contacted and reacted, and then the solid product after the solvent is removed is dried to obtain a supported titanium sulfate catalyst.

6. The preparation method according to claim 5, wherein: The alcohol aqueous solution is a methanol-water mixed solution, an ethanol-water mixed solution or an isobutanol-water mixed solution; Preferably, the weight ratio of alcohol to water in the alcohol aqueous solution is 1:(0.1-10), preferably 1:(0.2-5).

7. The preparation method according to claim 5, wherein: The weight ratio of the titanium sulfate, the alcohol aqueous solution and the illite mesoporous composite material is 1:(3-100):(1.5-9), preferably 1:(5-20):(1.8-6).

8. The preparation method according to claim 5, wherein: The contact reaction conditions include: temperature of 50-90° C. and time of 0.5-12 h.

9. Use of the supported titanium sulfate catalyst according to any one of claims 1 to 4 in the synthesis reaction of methyl methacrylate.

10. The use according to claim 9, wherein: The application comprises: simultaneously contacting methacrylic acid and methanol with a supported titanium sulfate catalyst; And / or, the contact conditions include: the contact temperature is 40-150°C, preferably 60-120°C; the contact pressure is 0.01-5MPa, preferably 0.1-3Mpa; the mass space velocity of methacrylic acid is 0.01-30h -1 , preferably 0.1-10h -1 ; The mass space velocity of methanol is 0.01-50h -1 , preferably 0.1-30h -1 .

Citation Information

Patent Citations

  • Method for preparing tributyl citrate through diatomite immobilized titanium sulfate used as catalyst

    CN102584591A

  • Spherical zeolite mesoporous composite material and supported catalyst, and preparation methods and application of spherical zeolite mesoporous composite material and supported catalyst, and preparation method of ethyl acetate

    CN104415795A

  • Isobutane dehydrogenation catalyst with supporter being spherical double-mesoporous illite composite material, as well as preparation method and application thereof

    CN110614106A

  • Catalyst for synthetic reaction of methyl methacrylate as well as preparation method and application of catalyst

    CN114515598A

  • Supported catalyst as well as preparation method and application thereof in synthesis of methyl methacrylate

    CN115487865A